Methods for the formation of monologue speech in the Russian language classes in a non-linguistic university - Akisheva, Zh.S.; Kucherenko, O.F.; Zulpukarov, K.Z.; Yushko, N.F.; Rapisheva, Zh.D. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
In the article topical issues of teaching Russian as a foreign language in Kazakh language groups were considered. The authors focus on the topical problem of forming the skills of monological speech at the basic and academic levels. Based on the practical experience of working in the basic and academic level groups in a technical university the authors analyze the effectiveness of the very method of combining multilevel groups and working on the monological speech with the use of innovative methods. In this article on the example of particular classes such methods as “Tandem”, excursion, case-study, project were studied in the aspect of working out the skills of monological speech. The authors offer the plan of organizing classes at different levels of groups, defining the ratio of topics and the most adequate methods aimed at forming skills of monological speech in the course of studying these topics.
Тілдік емес жоғары оқу орындағы орыс тілі сабақтарында монологтік сөйлеуді қалыптастыру әдістері
Методы формирования монологической речи на занятиях по русскому языку в неязыковом вузе
Keywords: Russian language; monologue speech; innovative methods; teaching methods; multi-level groups; technical university; topical issues; organization of classes